The ANALYSIS OF FORECASTING OF FARMER EXCHANGE RATE FOR THE FOOD CROP SUBSECTOR IN NORTH SUMATRA PROVINCE USING ARIMA METHOD - Siagian, Andreas (Universitas Gajah Putih, 2026)
One of the measurements the level of farmer welfare is by calculating the Farmer Exchange Rate (NTP). This study aims to analysis of forecasting and describe the results of forecasting the farmer exchange rate (NTP) for the food crop subsector in 2025-2027 using the ARIMA method. This research employs descriptive and econometric analysis using time series NTP for the food crop subsector from January 2020 to December 2024 in North Sumatra Province, obtained from the BPS SUMUT website. This study shows that the best forecasting model is ARIMA (2,1,0) and the forecasting results show an increasing trend, but the NTP value < 100 percent, so food crop farmers in North Sumatra are not yet wealthy.